The Impact of English Slang in Indonesian Efl Students to Enhance Student’s Speaking Skill - Zahratul Fitri Annapis; M. Adib Nazri; Astrid Dwimaulani (Mataram University, 2026)
English speaking proficiency remains a challenge for many Indonesian EFL students due to limited opportunities to practice authentic communication and low self-confidence in using the language. Since English slang is commonly used in everyday communication and digital media, it has the potential to create a more engaging and natural speaking environment for students. This study aimed to investigate the impact of English slang on Indonesian EFL students’ speaking skill. A qualitative research design was employed involving 17 tenth-grade students at a vocational high school in Indonesia. Data were collected through observation checklists, speaking performance assessments, students’ self-reflection questionnaires, and documentation. The students participated in pair conversations on various topics and were encouraged to use English slang expressions appropriately. The findings indicate that all students actively participated in the activity, used English to communicate, and incorporated slang expressions into their conversations. Most students achieved a rating of Good or Very Good in their speaking performance, particularly in terms of fluency, pronunciation, confidence, and the use of English slang. Self-reflection results also indicate that students felt more comfortable, confident, and motivated when speaking English using slang expressions. In addition, students felt that slang made conversations more natural and helped them express their ideas more easily. These findings suggest that English slang can positively support students’ speaking skills by boosting their self-confidence, participation, fluency, and communicative engagement in EFL classrooms.